1986
DOI: 10.1152/jappl.1986.61.1.361
|View full text |Cite
|
Sign up to set email alerts
|

Contractile changes in opposing muscles of the human ankle joint with aging

Abstract: The effects of aging on maximal voluntary strength and on the isometric twitch were determined in the ankle dorsiflexor and plantarflexor muscles of 111 healthy men and women aged 20-100 yr. Men were found to be stronger than women at all ages. In both sexes, the average values for maximum voluntary strength of the dorsiflexors and plantarflexors began to decline in the 6th decade. Although the absolute loss of strength was greater for the plantarflexor muscles, the relative losses were similar in the two musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
318
5
15

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(400 citation statements)
references
References 0 publications
62
318
5
15
Order By: Relevance
“…and thus are "useful to study physiological mechanisms…independent of the maximal generated force" (Holtermann et al 2007). A potential factor influencing the age-related reduction in relative RFD may be attributed to changes in motor unit recruitment and/or activation patterns (Vandervoort and McComas 1986;Klass et al 2008). For example, Klass et al (2008) have reported that the age-related reduction in RTD was accompanied by a decrease in motor unit discharge rates and the percentage of motor units that discharged with doublets in the old men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and thus are "useful to study physiological mechanisms…independent of the maximal generated force" (Holtermann et al 2007). A potential factor influencing the age-related reduction in relative RFD may be attributed to changes in motor unit recruitment and/or activation patterns (Vandervoort and McComas 1986;Klass et al 2008). For example, Klass et al (2008) have reported that the age-related reduction in RTD was accompanied by a decrease in motor unit discharge rates and the percentage of motor units that discharged with doublets in the old men.…”
Section: Discussionmentioning
confidence: 99%
“…These and previous findings may suggest that the agerelated declines in relative rapid force characteristics may be attributed to factors other than the impairment of rapid muscle activation in healthy older adults. For example, it is possible that these reductions may be due to the agerelated changes in muscle contractile mechanics (Brooks and Faulkner 1988) and properties (Vandervoort and McComas 1986), reduction in the number and size of type II fibers (Aagaard et al 2007;Lexell 1995), decrease in muscle quality resulting from the increased accumulation of fat and connective tissue and concomitant decline in muscle mass (Lexell 1995), and structural or architectural changes such as reduced tendon stiffness, pennation angles, and fascicle lengths (Narici et al 2003). However, further research is necessary to elucidate the mechanisms associated with age-related loss in relative rapid force capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5,6,7,8,9,10,11,12] . However, the methods employed in these early studies were not particularly sensitive and higher resolution techniques [eg.…”
Section: Figurementioning
confidence: 99%
“…The original twitch interpolation technique described by Merton [3] and subsequently employed by many others [1,5,6,7,8,9,12,14,29] involved a single stimulus interpolated over voluntary contractions. Recently it has become common for 2 or more stimuli (50-100 Hz) to be employed [17,18,34,38,51] because the evoked force increments are larger and more readily detected [15,32,43,45,54,55,56,57,58] .…”
Section: The Number Of Interpolated Stimulimentioning
confidence: 99%
“…This can be seen by an increase in muscle atrophy, common in type II fibers, 1 which is related to the reduction of maximal voluntary strength. [2][3][4] The impairment of muscle development and function with age tends to accelerate after the age of 50 years 5 and is linked with increases in falls and fractures, as well as a decreased capacity to recover from such injuries. 6 Sarcopenia has an important socioeconomic consequence as falls are a major source of morbidity and mortality in the increasing population of the elderly.…”
Section: Introduction Smentioning
confidence: 99%